2018
DOI: 10.1007/s10911-018-9407-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 Derived from Mammary Fibroblasts Promotes Progression of Mammary Lesions to Invasive Carcinoma through CXCR2 Dependent Mechanisms

Abstract: With improved screening methods, the numbers of abnormal breast lesions diagnosed in women have been increasing over time. However, it remains unclear whether these breast lesions will develop into invasive cancers. To more effectively predict the outcome of breast lesions and determine a more appropriate course of treatment, it is important to understand the underlying mechanisms that regulate progression of non-invasive lesions to invasive breast cancers. A hallmark of invasive breast cancers is the accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 110 publications
1
15
0
Order By: Relevance
“…Moreover, one hypothesis for the increase in CXCR2 positive cells could be the higher release of CXCR2 ligands by other cells. In particular, we and others have shown that both CXCL1 and CXCL8, ligands of CXCR2, could be produced at higher levels by mesenchymal stem cells or fibroblasts, which have been "educated" by TNBC cells [16,33,34]. Similar overexpression of CXCR2 ligands occurs also for breast cancer cells and could represent another source of chemokines production [9,[12][13][14]19].…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, one hypothesis for the increase in CXCR2 positive cells could be the higher release of CXCR2 ligands by other cells. In particular, we and others have shown that both CXCL1 and CXCL8, ligands of CXCR2, could be produced at higher levels by mesenchymal stem cells or fibroblasts, which have been "educated" by TNBC cells [16,33,34]. Similar overexpression of CXCR2 ligands occurs also for breast cancer cells and could represent another source of chemokines production [9,[12][13][14]19].…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, fibroblasts are a key component of breast cancer stroma and a determinant of breast cancer progression (Ahn et al, 2012;Cid et al, 2018;Kalluri and Zeisberg, 2006). Their protumorigenic effects include production of paracrine proliferative and proinvasive signals to cancer cells (Bernard et al, 2018;Orimo et al, 2005), ECM remodeling to enable invasion of cancer cells (Gaggioli et al, 2007) and enabling immune evasion (Chakravarthy et al, 2018). Because increased expression of FGF ligands, including FGF1, FGF2 and FGF7, was found in breast cancer stroma in comparison with normal breast stroma (Finak et al, 2008;Relf et al, 1997), it is relevant to investigate the role of FGF signaling in breast cancer-associated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves inhibition of CAF-mediated proteolysis of the extracellular matrix in part through inhibiting the production of CAF-derived IL-6 [31]. Another recently identified CAF-derived factor that promotes invasion of in situ mammary lesions is the chemokine CXCL1 [64]. Using the MMTV-PyMT model on the C57BL/6 background, Bernard et al [64] demonstrated that CXCL1 produced by CAFs isolated from tumors in MMTV-PyMT mice promoted invasion of epithelial cells using a co-transplant model.…”
Section: Fibroblasts In Dcismentioning
confidence: 99%
“…Another recently identified CAF-derived factor that promotes invasion of in situ mammary lesions is the chemokine CXCL1 [64]. Using the MMTV-PyMT model on the C57BL/6 background, Bernard et al [64] demonstrated that CXCL1 produced by CAFs isolated from tumors in MMTV-PyMT mice promoted invasion of epithelial cells using a co-transplant model. This was dependent upon fibroblastderived CXCL1, which promoted invasion through CXCR2 and activation of downstream signaling pathways, including extracellular regulated kinase (ERK), nuclear factor kappa B (NFκB), Akt and signal transducer and activator of transcription 3 (STAT3) [64].…”
Section: Fibroblasts In Dcismentioning
confidence: 99%